A formação inicial do professor de inglês: o olhar do aluno - Périllat, Luciana Hortense Garcia (2011)
The aim of this research is to investigate a pre-service English teacher education course in São Paulo by offering a critical-analytical view not only of its organization but also of the pedagogical-practical curriculum itself. The investigation was done by: (a) a study of the curriculum for the course; (b) class observation; (c) plans for some subjects; (d) the students view of the course. A panoramic view was built based on the curriculum, the curriculum in practice and on how the students see the course they have been doing. The theoretical basis for this research involves: (a) teacher educators and future teachers as engaged human beings involved in change (Freire, 1996/2005); (b) a view of an autonomous teacher-researcher involved in practice (Vygotsky 1979/ 2004); (c) the view of an educator as an autonomous researcher; (d) the curriculum as an instrument for research about reality (Apple, 2006). The data were collected using a questionnaire, observing classes in the undergraduate course and analyzing the curriculum for the course as well as the plans for some disciplines. This analysis allowed for a broad view of how the English Language Course is organized and of how the future teachers feel about the course